Sandpoint at the north end of the long bridge [videorecording (VHS)] - Compton, Sandy; Daarstad, Erik (City of Sandpoint, 2002)
This documentary film about Sandpoint, Idaho includes selections of personal interviews and contemporary footage as well as black and white and color still images, and weaves a compelling history of Sandpoint, the town at the north end of the long bridge.